2013
DOI: 10.1002/imhj.21390
|View full text |Cite
|
Sign up to set email alerts
|

Dads' Parenting Interactions with Children: Checklist of Observations Linked to Outcomes (PICCOLO‐D)

Abstract: Intervention programs aiming to support fathers’ parenting skills with young children need a practical, but psychometrically sound, observational measure of fathers’ parenting interactions. The purpose of this study was to test the psychometric properties of the Parenting Interactions with Children—Checklist of Observations Linked to Outcomes (PICCOLO) measure for use with fathers, and to explore whether additional observational father‐behavior items derived from father research and theory would strengthen tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 64 publications
(95 reference statements)
2
45
0
1
Order By: Relevance
“…Indeed, studies show that positive parenting is associated with higher levels of child social competence (Heinonen, Räikönnen, & Keltikangas‐Järvinen, ; Schneider, Atkinson, & Tardif, ). For example, Anderson, Roggman, Innocenti, and Cook () found that high levels of affection and responsiveness were associated with children's socioemotional outcomes in prekindergarten. Additionally, Rispoli and colleagues () found that parental responsiveness during the preschool years was associated with child social competence at entry to kindergarten.…”
Section: Couple Interaction Parent–child Interaction and Attachmentmentioning
confidence: 99%
“…Indeed, studies show that positive parenting is associated with higher levels of child social competence (Heinonen, Räikönnen, & Keltikangas‐Järvinen, ; Schneider, Atkinson, & Tardif, ). For example, Anderson, Roggman, Innocenti, and Cook () found that high levels of affection and responsiveness were associated with children's socioemotional outcomes in prekindergarten. Additionally, Rispoli and colleagues () found that parental responsiveness during the preschool years was associated with child social competence at entry to kindergarten.…”
Section: Couple Interaction Parent–child Interaction and Attachmentmentioning
confidence: 99%
“…In the context of the coparenting system, observed similarities between mother and father behavior might at least partially reflect the influence each has on the other's behavior. These cross-parent influences are domain specific (Anderson, Roggman, Innocenti, & Cook, 2013).…”
Section: Fathers and Mothers Are Similarmentioning
confidence: 99%
“…The PICCOLO Affection subscale measured at 24 months was positively correlated with children's 36‐month and preschool‐age receptive vocabulary and cognitive development in the original validation sample (Roggman et al., ). With the PICCOLO‐D, a modified version used to assess father–child interactions, affection at 24 months was associated with 36‐month receptive vocabulary and cognitive development as well as preschool‐age receptive vocabulary, cognitive development, and emotion regulation (Anderson, Roggman, Innocenti, & Cook, ). Total PICCOLO scores (all four subscales combined) followed a similar pattern for children with special needs (Innocenti, Roggman, & Cook, ).…”
Section: Measuring Adult–child Interactionsmentioning
confidence: 99%
“…Mothers’ responsiveness at 24 months has been positively correlated with children's receptive vocabulary and cognitive development at 36 months and children's receptive vocabulary, cognitive development, and letter‐word recognition in preschool (Roggman et al., ). Fathers’ responsiveness at 24 months has been positively associated with children's 36‐month and preschool‐age receptive vocabulary, cognitive development, and emotion regulation (Anderson et al., ).…”
Section: Measuring Adult–child Interactionsmentioning
confidence: 99%
See 1 more Smart Citation